Answer:
Step-by-step explanation:
Orbital radius of satellite A , Ra = 6370 + 6370 = 12740 km
Orbital radius of satellite B , Rb = 6370 + 19110 = 25480 km
Orbital potential energy of a satellite = - GMm / r where G is gravitational constant , M is mass of the earth and m is mass of the satellite
Orbital potential energy of a satellite A = - GMm / Ra
Orbital potential energy of a satellite B = - GMm / Rb
PE of satellite B /PE of satellite A
= Ra / Rb
= 12740 / 25480
= 1 / 2
b ) Kinetic energy of a satellite is half the potential energy with positive value , so ratio of their kinetic energy will also be same
KE of satellite B /KE of satellite A
= 1 / 2
c ) Total energy will be as follows
Total energy = - PE + KE
- P E + PE/2
= - PE /2
Total energy of satellite B / Total energy of A
= 1 / 2
Satellite B will have greater total energy because its negative value is less.